2021
DOI: 10.1002/jat.4231
|View full text |Cite
|
Sign up to set email alerts
|

Propyl gallate decreases the proliferation of Calu‐6 and A549 lung cancer cells via affecting reactive oxygen species and glutathione levels

Abstract: Propyl gallate (3,4,5-trihydroxybenzoic acid propyl ester, PG) has an anti-proliferative effect in various cells. In this study, Calu-6 and A549 lung cancer cells were used to examine the anti-proliferative effect of PG in relation to reactive oxygen species (ROS) and glutathione (GSH) levels. PG (100-1,600 μM) dose-dependently inhibited the proliferation of Calu-6 and A549 cells at 24 h, and PG at 800-1,600 μM strongly induced cell death in both cell lines. PG (800-1,600 μM) increased cellular metabolism in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…14 Furthermore, increasing studies have identified that oxidative damage caused by PG is an important route of PG performs its cytotoxicity, and PG either increases or decreases ROS level depending on its dose and time of exposure. 57 In our study, exposure to PG increased the level of ROS in oocytes and induced apoptosis, which is consistent with the above data. Given that ROS has been confirmed as a crucial way of multiple environmental toxicants to exert harmful influences in female reproduction, 23,39,[58][59][60] we conjectured that PG induced the elevation of ROS in oocytes is responsible for mitochondria dysfunction, ATP depletion and DNA damage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…14 Furthermore, increasing studies have identified that oxidative damage caused by PG is an important route of PG performs its cytotoxicity, and PG either increases or decreases ROS level depending on its dose and time of exposure. 57 In our study, exposure to PG increased the level of ROS in oocytes and induced apoptosis, which is consistent with the above data. Given that ROS has been confirmed as a crucial way of multiple environmental toxicants to exert harmful influences in female reproduction, 23,39,[58][59][60] we conjectured that PG induced the elevation of ROS in oocytes is responsible for mitochondria dysfunction, ATP depletion and DNA damage.…”
Section: Discussionsupporting
confidence: 93%
“…Published data suggested that the anti‐oxidative and cytoprotective properties of PG could change to pro‐oxidative, cytotoxic and genotoxic properties in the presence of Cu(II) 14 . Furthermore, increasing studies have identified that oxidative damage caused by PG is an important route of PG performs its cytotoxicity, and PG either increases or decreases ROS level depending on its dose and time of exposure 57 . In our study, exposure to PG increased the level of ROS in oocytes and induced apoptosis, which is consistent with the above data.…”
Section: Discussionmentioning
confidence: 99%
“…PG is a synthetic agent that has anti-growth effects in many cell types, including endothelial cells [27,28], leukemia cells [29], breast cancer [30], hepatocellular carcinoma cells [31], and cervical cancer cells [6,32]. Recently, our group has found that PG treatment inhibits the growth of lung cancer cells, especially A549 epithelial adenocarcinoma cells via apoptosis or GSH depletion [33,34]. Fibroblast cells are the most abundant type of cells in the pulmonary interstitium.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related deaths worldwide [ 29 ]. Recently, we reported that PG treatment inhibited the growth of lung cancer cells through apoptosis or GSH depletion [ 30 , 31 ]. In the present study, the anti-apoptotic effects of various pan-caspase, caspase-3, caspase-8, and caspase-9 inhibitors were investigated in PG-treated Calu-6 and A549 lung cancer cells in relation to changes in ROS and GSH levels.…”
Section: Introductionmentioning
confidence: 99%